Spanish New Orleans and the Caribbean = La Nueva Orleans y la Caribe españoles - Lemmon, Alfred Emmette 1949- (The Historic New Orleans Collection, 2022)
"The essays in this catalog, and the objects included in the exhibition it commemorates, were selected to promote a greater understanding of Spanish colonial Louisiana. Among the diverse themes of the exhibition is the strong link-administrative, cultural, and economic-between New Orleans and the far larger and more important Spanish cities such as Havana, Mexico City, Santo Domingo, Santiago de Cuba and Veracruz"--